2013
DOI: 10.1542/peds.2012-1651
|View full text |Cite
|
Sign up to set email alerts
|

Presleep Activities and Time of Sleep Onset in Children

Abstract: Screen sedentary time dominated the presleep period in this sample and was associated with a later sleep onset. The development of interventions to reduce screen-based behaviors in the presleep period may promote earlier sleep onset and ultimately improved sleep duration in young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 25 publications
4
59
2
3
Order By: Relevance
“…A longitudinal study that tracked New Zealand youth between the ages of 5 and 15 found similar results showing increased television exposure in childhood leading to increased attention problems in the teenage years (Landhuis, Poulton, Welch, & Hancox, 2007). Finally, another study examined the specific impact of television viewing on sleep quality and found that more television viewing in the last 90 min before sleep resulted in worse sleep quality in children (Foley et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study that tracked New Zealand youth between the ages of 5 and 15 found similar results showing increased television exposure in childhood leading to increased attention problems in the teenage years (Landhuis, Poulton, Welch, & Hancox, 2007). Finally, another study examined the specific impact of television viewing on sleep quality and found that more television viewing in the last 90 min before sleep resulted in worse sleep quality in children (Foley et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…A 2010 review of 36 youth studies from around the world linked use of such devices prior to sleep with late sleep and wake times and short sleep duration [22]. Night time technology use is also linked with functional impact including increased sedentary behaviour prior to bed [23], subjective poor sleep quality [24], greater caffeine consumption, falling asleep in school and increased daytime sleepiness [25].…”
Section: Introductionmentioning
confidence: 99%
“…Az internetezéssel eltöltött idő hossza összefüggött a serdülő testsúlyának növekedésével, ezzel párhuzamosan az alvással töltött idejük csökkent (Do, Shin, Bauta, & Foo, 2013), inszomnia alakult ki (Cheung & Wong, 2011). Az elalvást megelőző 90 percben történő internetezés rontott az alvás minőségén a vizsgált gyermekek körében (Foley et al, 2013). Mások szerint a fizikai egészségre is rossz hatással van a problémás internethasználat (Kelley & Gruber, 2013).…”
Section: A Problémás Mértékű Internethasználat Hatása Az Iskolai Teljunclassified